Indoor air fungal population in movie theaters of shopping malls in Iloilo City - Dureza, Christine Joy.; Flores, Erl Addison; Gallega, Mary Carmel Frances (2005.)
The study aimed to determine the profile of indoor air fungal population in selected movie theaters of shopping malls in Iloilo City. This study will be valuable to the management of the different shopping malls. It will provide significant knowledge and awareness on the occurence of various fungi and fungal load in their respective theaters., Fungal were collected in January 2005, by exposing agar plates in nine movie theaters located in three malls in Iloilo City. Air sampling was done by exposing Potato Dextrose Agar plates in three operating periods: opening, mid, and closing hours. Fungi were identified to the genus level only and classified up to the phylum level only. Species were then compared within and among malls. A total of 15 species were isolated and among these, Mycelia sterilia, Asperigillus spp, Mucor spp, Penicillium spp, and Rhizopus sp. were the frequently occuring species. Fungal load was computed and compared between and among theaters. However, one-way and Nested ANOVA showed no significant difference within and among malls. Temperature and relative humidity were also monitored to determined their effect on the occurence of fungi. However, through Pearson's correlation, the mean fungal load in theaters showed significant (P<0.014) inverse relationship with the mean relative humidity (r=0.273).
Special Study (Undergraduate, Bachelor of science in Public Health) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Health and hygiene -- Theaters -- Iloilo City